Multi-scenario simulation of LULC and carbon dynamics in karst regions using the PLUS model - Ding, Caixia; Zhou, Zhongfa; Wang, Cui; Kong, Jie; Wang, Yanbi; Xie, Rukai (Frontiers in Environmental Science, 2025)
Land cover change is an important cause of carbon source/sink changes in terrestrial ecosystems. Studying the relationship between land use transition and carbon sources/sinks is of great significance for optimizing regional land use planning, achieving sustainable development, and the “double carbon” goals. Land cover change significantly impacts carbon sources and sinks in terrestrial ecosystems, making the study of land use transition crucial for optimizing regional planning and achieving sustainable development and carbon neutrality goals. This research analyzes carbon effects of land use changes in Pingzhai Reservoir watershed (2010–2020) using carbon effect coefficient method, and employs PLUS model to simulate 2030 scenarios (natural development, cropland protection, economic priority). Results show net carbon emissions increased 64.92% (from 121,558.73 to 200,477.90 tons), with built-up land becoming the main carbon source (167% growth) while forests contributed over 90% of carbon sequestration. All scenarios predict rising emissions by 2030, suggesting the need to control production land expansion, accelerate agricultural innovation, and promote low-carbon development. The study applies PLUS model to karst mountain areas, quantifying land use-carbon emission relationships through scenario simulations to support ecological conservation and low-carbon strategies in fragile regions.